Comfort temperature of air-conditioning living room with various set point of temperature under hot-humid climate - Kamaruddin, Nurul Izzati (2021)
The use of an air-conditioner (AC) becomes essential in residential buildings, particularly in a hot and humid climate, to provide a comfortable environment for human activities. There is a scarcity of significant research exploring thermal comfort for residential buildings with AC usage and indoor comfort temperature on various AC settings based on the sensitivity and assessment of thermal comfort requirements in the living room area. Moreover, the behavior of AC set point practice for non-commercial buildings, which is recommended to be not below than 24°C, is not stated in the guidelines and standards mentioned for government office buildings in Malaysia. Thus, this study aims to evaluate the personal characteristics and adaptive behavior, estimate the comfort temperature at various indoor temperatures and compare the established comfort temperature with related local and international standards. The field measurement and survey has been carried out in two living rooms located in Universiti Teknologi Malaysia, Kuala Lumpur and Universiti Malaysia Pahang, Pekan at four different AC set point temperatures (i.e., 16C, 20C , 24C , and 28C ) for 63 university students with 252 samples collected. The mean indoor thermal parameters were measured within a 10 s time interval. The Chi-square results indicated that the difference in gender and body mass index had no significant effect on the thermal sensation of respondents, while the water intake and clothing insulation level affect personal thermal comfort. Besides, the results of Griffiths’ method had disclosed that the mean comfort temperature based on operative temperature for respondents was found to be 24.3C, which is within the range of indoor thermal comfort zone of 2 3 C and 27C , as recommended by local and international standards. It is essential to provide the owner with guidelines to set the AC temperature above the established comfort temperature to fit the buildings’ functionality. It would be beneficial towards achieving better health, saving power, and reducing electricity consumption while maintaining the thermal comfort requirements, especially in Malaysia and other countries experiencing hot and humid climate.